Cluster Entrepreneurship Development in Lithuania Best Practice - Margarita Išoraitė (Integrated Journal of Business and Economics (IJBE), 2019)
Clusters becoming important field in Lithuania. Clusters aim to join forces to gain mutual benefits, accelerate the process of developing new products, services or technologies, and bring them to market, foster innovation and collaborate on science and business. Clusters in Lithuania have benefit:  stimulates innovation and growth, promotes the transfer of knowledge and helps develop new ideas and business, promotes export development, contributes to the internationalization of enterprises, helps to reach foreign markets and find new business partners, helps attract new technologies, skilled labor, investment in research and development and innovation, strengthens the human, technical, scientific, capital, innovation, partnership and other capabilities of individual cluster members, provides access to unique, specialized resources and enhances the competitive advantage of cluster members, helps to reduce the costs of small and medium-sized enterprises,  prepare SMEs for growth,  helps reduce risk and increases the likelihood of success in selecting new R&D trends.